A Seat at the Table: Using Social Media as a Platform to Resolve Microaggressions Against Transgender Persons. Issue 3 (3rd July 2017) - Ingram, Mercedes V.; Speedlin, Stacy; Cannon, Yuliya; Prado, Ashley; Avera, Joe
ABSTRACT: Transgender, gender variant, and/or gender nonconforming persons are marginalized and pathologized in society and communities. The advent and widespread use of social media introduce an entirely new avenue of expression where cyber bullying and verbal assaults are common. Yet, social media also has the capacity to reach more people in more places, thus presenting a potentially powerful platform for advocacy. Grounded in digital critical participatory action research, the authors present a multimedia advocacy project that highlights advocacy strategies in which counselors can utilize social media to raise awareness, promote inclusion, and resolve microaggressions toward transgender persons.